2020
DOI: 10.1002/ppul.24670
|View full text |Cite
|
Sign up to set email alerts
|

Is out‐patient based treatment of bronchiectasis exacerbations in children comparable to inpatient based treatment?

Abstract: Background and Objective Children with bronchiectasis have recurrent exacerbations and may require hospitalization. “Hospital in the home (HITH)” is used as an alternative to hospitalization for children with cystic fibrosis (CF) but to date, there is no published data on children without CF. We describe our experience of HITH (intravenous [IV] antibiotics and at least once‐daily physiotherapy‐treated airway clearance therapy) in a cohort of children with bronchiectasis, comparing outcomes between hospital and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
0
7
0
1
Order By: Relevance
“…Hospitalization resource use data for each patient was determined and costed by the QCH Finance Department applying the Independent Hospital Pricing Authority (IHPA) Hospital Patient Costing Standards v3.1 (July 2014) 20. Children receiving HITH had daily nursing visits for antibiotics and twice daily physiotherapist visits for airway clearance therapy, similar to the care received in hospital (Appendix S1 in Supplementary Information) 21…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hospitalization resource use data for each patient was determined and costed by the QCH Finance Department applying the Independent Hospital Pricing Authority (IHPA) Hospital Patient Costing Standards v3.1 (July 2014) 20. Children receiving HITH had daily nursing visits for antibiotics and twice daily physiotherapist visits for airway clearance therapy, similar to the care received in hospital (Appendix S1 in Supplementary Information) 21…”
Section: Methodsmentioning
confidence: 99%
“…20 Children receiving HITH had daily nursing visits for antibiotics and twice daily physiotherapist visits for airway clearance therapy, similar to the care received in hospital (Appendix S1 in Supplementary Information). 21…”
Section: Data Sourcesmentioning
confidence: 99%
“…However, due to limited numbers of patients with non-CF bronchiectasis and PCD during the study period we could not make any firm conclusions about the benefit of the model of care regarding this cohort. Although a recent study by O'Rourke et al [22] indicates that children with non-CF bronchiectasis can be managed safely at home while achieving comparable outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Issues of note include increased absenteeism from school, carer's leave and high levels of antibiotic use when treated in hospital [20]. Two other recent studies found that children with non-CF bronchiectasis could be safely managed within the home environment and achieve comparable outcomes while reducing healthcare costs [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…clearly shows that longer length of hospital stays and not receiving treatment by hospital in the home services significantly contribute to increased healthcare costs. Observational studies in adults and children with bronchiectasis have shown that home‐based treatment for exacerbations was safe, and resulted in less morbidity, and was as effective as hospital‐based treatment, including similar clinical and quality of life improvement and 30‐day readmission rates, and significantly reduced the hospitalization days, thus reducing the healthcare costs 7 . Potential advantages of outpatient provision of intravenous antibiotics in patients with bronchiectasis go beyond cost reductions but include reducing the risk of cross‐infection, improvement in patient's quality of life by spending less time in hospital and less disruption to family life.…”
mentioning
confidence: 99%